Factors Influencing Customer Interest in Adopting Online Banking Services: A Descriptive Study at BRI Unit Indihiang - R. Hozin Abdul Fatah; Siti Amirah Makarim; Sani Haryati (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study examines the factors influencing customer interest in online banking (e-banking) adoption at PT Bank Rakyat Indonesia (Persero) Tbk. Unit Indihiang, analyzes the role of bank employees in promoting e-banking usage, and documents available e-banking services and their operational mechanisms. A descriptive qualitative method was applied, with primary data obtained through observation and semi-structured interviews, and secondary data via documentation and literature review. Findings reveal three core adoption drivers: knowledge (especially regarding device accessibility and risk awareness), trust (particularly data security and transaction notification reliability), and perceived usefulness (including time efficiency, transaction diversity, and cost reduction). Bank employees across all positions unit head, tellers, customer service officers, field officers, and security guards collectively constitute a multi-layered adoption ecosystem. These findings are intended to inform strategies for improving e-banking socialization and adoption at the branch level.